The Effect of Group Work Activities to Improve Students’ Speaking Skill - Rospinah Rospinah; Andi Tenri Ampa; Syamsiarna Nappu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This research aimed to improve students’ speaking skill for the 8th grade students of MTs Syekh Yusuf Sungguminasa by applying group work activities (Think Pair Share, Snowball and Jigsaw) in teaching English and to find out whether Group Work Activities is more effective than the conventional method in improving students speaking skills. A quasi-experimental research method was used and a number of 40 students participated in this research. These students were divided into the Experimental Group (EG) and Control Group (CG), with each group consisted of 20 students. The instrument used for this study was speaking test and recording which were conducted as a pretest before the application of group work activities and a posttest after it. The students’ scores, as data of this research were analyzed by using SPSS 24. This research indicated significant improving of the students speaking skill by using group works activities than using conventional method. The posttest mean score: pronunciation EC (6.490) > CC (3.070), grammar EC (6.830) > CC (3.905), vocabulary EC (7.075) > CC (3.740) and fluency EC (6.670) > CC (3.915). The results of this research by using group work activities showed that the students speaking accuracy consisting of vocabulary, pronunciation and grammar and fluency was effectively improving students speaking skill than conventional method.